2013
DOI: 10.1186/1475-2859-12-44
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid fermentation as a tool to enhance the functional features of Echinacea spp

Abstract: BackgroundExtracts and products (roots and/or aerial parts) from Echinacea ssp. represent a profitable market sector for herbal medicines thanks to different functional features. Alkamides and polyacetylenes, phenols like caffeic acid and its derivatives, polysaccharides and glycoproteins are the main bioactive compounds of Echinacea spp. This study aimed at investigating the capacity of selected lactic acid bacteria to enhance the antimicrobial, antioxidant and immune-modulatory features of E. purpurea with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 62 publications
4
30
0
5
Order By: Relevance
“…Domains, located in the N-terminal proteolytic region of PlnG, are responsible for recognition and cleavage of the double-glycine leader peptides from precursors of various bacteriocins, such as the plantaricins J/K (17,26,57). Similar peptides were also found in the antimicrobial extract of Echinacea sp., which was also fermented with L. plantarum C2 (58). The MIC of the purified fraction, which contained the mixture of the identified peptides, was comparable to the MIC values previously reported for partially purified antimicrobial peptides produced by lactic acid bacteria (58,72).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Domains, located in the N-terminal proteolytic region of PlnG, are responsible for recognition and cleavage of the double-glycine leader peptides from precursors of various bacteriocins, such as the plantaricins J/K (17,26,57). Similar peptides were also found in the antimicrobial extract of Echinacea sp., which was also fermented with L. plantarum C2 (58). The MIC of the purified fraction, which contained the mixture of the identified peptides, was comparable to the MIC values previously reported for partially purified antimicrobial peptides produced by lactic acid bacteria (58,72).…”
Section: Discussionsupporting
confidence: 58%
“…Similar peptides were also found in the antimicrobial extract of Echinacea sp., which was also fermented with L. plantarum C2 (58). The MIC of the purified fraction, which contained the mixture of the identified peptides, was comparable to the MIC values previously reported for partially purified antimicrobial peptides produced by lactic acid bacteria (58,72). To the best of our knowledge, the antimicrobial activity of plantaricins J/K toward the Gram-negative E. coli was not found previously.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Subsequently, the dishes were incubated at 37°C for 48 h. After the formation of visible colonies, 10 mL of BBL culture medium (212207 -BD BBL™ Enterococcosel™, EEUU) were poured on the dishes, which contained 0.01 mL of the indicator pathogen strain with a concentration of 9.2x10⁷ UFC/mL and then were incubated at 37°C for 48 h. The antagonist activity was verified for the formation of transparent zones around the colonies greater than 1.0 mm. In order to verify the nature of the inhibition the described technique of Rizzello et al (13) was performed.…”
Section: A N T a G O N I S M D E T E R M I N A T I O N O F T H E Biopmentioning
confidence: 99%
“…(Rizzello & Coda 2013), and Malaysian herbal teas (Ibrahim, Mustafa & Ismail 2014). It was also reported that parts of plants experiencing the increase of total phenolic content after the fermentation (Ng et al 2014).…”
Section: Effect Of Lactic Acid Fermentation On Phenolic Compoundsmentioning
confidence: 99%